Comparison of green building policies and regulations between central and local governments of China: Analysis based on text similarity - Hu, Yuan; Lin, Yajing (Frontiers in Environmental Science, 2022)
The development of green buildings, as the focus of the construction field, is an inevitable choice to achieve the goal of carbon peaking and carbon neutralization. From the perspective of text similarity, this paper conducts a comparative study of the 14th Five-Year Plan for Building Energy Conservation and Green Building Development issued by the Ministry of Housing and Urban-Rural Development of the PRC in 2022 and sixteen local regulations on green buildings at provincial levels. The results show that: First, promoting energy-saving and green transformation of existing public buildings, promoting new green construction methods, strengthening green building management system construction and other contents, have the highest similarity value, indicating that these three contents have the highest overall notices in the legislation formulation level of green buildings in different regions; Second, the legal texts formulated by Tianjin and Shanghai are more in line with the requirements of the 14th Five-Year Plan than those of other provinces, showing the forward-looking nature of local legislation; Lastly, through data analysis, it is found that the average similarities of the three deployments of green buildings have small differences, but there are large differences between regions. Jiangxi, Qinghai and Guangdong have some outstanding contents, forming regional characteristics according to local conditions, showing the differences of local legal texts. Since the Plan is the latest national guidance, it requires local regulations to refine and implement the contents of the Plan. Based on the comprehensive comparative analysis of the text, it is recommended that all localities should check and fill gaps according to the Plan, improve the key task systems and use local standards to build legal guarantee tailored to local conditions.